Male Hypogonadism : Basic, Clinical and Therapeutic Principles - Winters, Stephen J.; Huhtaniemi, Ilpo T. (Springer International Publishing : Imprint: Humana Press, 2017)
Now in a revised second edition, this comprehensive text covers all aspects of male hypogonadism from the basic science to clinical management, comprehensively explaining and applying new insights to the treatment of hypogonadal men. Chapters covering neuroendocrine control of testicular function, Leydig cell function, spermatogenesis, and normal and delayed puberty open the book. The focus then turns to the pathophysiology and treatment of hypogonadism and other forms of testicular dysfunction, such as Klinefelter syndrome, cryptorchidism, and disorders of the pituitary, as well as reproductive and endocrine consequences of cancer treatment, environmental factors, obesity and aging. Next are chapters that describe the available options for androgen replacement therapy, and the outcomes when men with hypogonadism of various causes are treated with testosterone, as well as a chapter devoted to current approaches to stimulating spermatogenesis in gonadotropin-deficient men. < Highly practical and updated with the latest available data, this second edition of Male Hypogonadism: Basic, Clinical and Therapeutic Principles cogently presents a large body of scientific information on male reproductive endocrinology to provide a thorough understanding of the pathophysiology, clinical characteristics, and treatments for disorders that adversely affect testicular function.
Keywords: Medicine.; Endocrinology.; Reproductive medicine.; Andrology.; elektronické knihy; electronic books